Self‐serving attributions, managerial cognition, and company performance - Clapham, Stephen E.; Schwenk, Charles R. (Strategic Management Journal, 1991)
Abstract Past research using managers' attributions for good and poor performance in annual reports has repeatedly demonstrated that management takes credit for good outcomes. However, there is disagreement about whether this pattern of attributions reflects attempts to manage impressions in stakeholders or biased perceptions on the part of management, and whether it is associated with increases or decreases in future performance. In this study, attributions in letters to shareholders in the annual reports of public utilities were analyzed. The results showed the same general pattern of attributions as was found in previous studies. However, the relationship between this pattern of attributions and performance (earnings per share growth) was generally negative. Implications of these results for future research are discussed.